Karakteristik pioderma superfisialis pada bayi dan anak di SMF Ilmu Kesehatan Kulit dan Kelamin RSUP H. Adam Malik Medan periode Januari 2010 – Desember 2012 - Rizky Kurniawan; Kristo A. Nababan; Salia Lakswinar (Fakultas Kedokteran USU, 2013)
Introductions : Superficial pyoderma is skin infection that located under stratum corneum until dermis or hair follicle.Objective : To identify the characteristic of superficial pyoderma in infants and children at Department of Dermatology and Venereology, H. Adam Malik General Hospital Medan, from period of January 2010 to December 2012. Methods : Retrospective study was carried out from medical records of superficial pyoderma patients in infants and children who had visited to Department of Dermatology and Venereology, H. Adam Malik General Hospital Medan, from period of 2010- 2012.Results : There were total 87 superficial pyoderma cases in infants and children, consist of 52.9% boys and 47.1% girls. Most common case was found in 1-5 years age group as much as 47.1%. The most common clinical presentation was bullous impetigo at 43.7%. The locations of superficial pyoderma lesions in infants and children showed relatively different annually. The locations of superficial pyoderma lesion in order from 2010-2012 are as followed; in the facial area was 31.0%, lower hands, armpit and lower limbs were 21.4% each, facial and armpit were 23.5% each. The treatment in infants and children usually using combination therapy depends on each clinical types.Conclusion: The most common case of superficial pyoderma in infants and children at Department of Dermatology and Venereology, H. Adam Malik General Hospital Medan were found in boys of 1-5 years age group. The most common clinical presentation was bullous impetigo. Each year showed different locations. The general treatment of superficial pyoderma in infants and children is topical antibiotics.Keywords : superficial pyoderma; retrospective study; characteristics